The Role of Land Deed Officials (PPAT) in Prevention of Money Laundering Criminal Acts Through The Implementation of the Principle of Knowing Service Users in Land Sales And Purchase Transactions In Pekanbaru City - Chintya Sari, Firna (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Money Laundering (TPPU) is a crime committed through various sectors, including the land sector, which is often exploited to disguise the origins of illegal funds. In this context, Land Deed Officials (PPAT) have a crucial role because they are directly involved in land sale and purchase transactions and are required to implement the Principle of Recognizing Service Users (PMPJ) as stipulated in Law Number 8 of 2010, Government Regulation Number 43 of 2015, and Regulation of the Minister of ATR/BPN Number 21 of 2022. This study aims to analyze the position of PPAT in preventing TPPU from a legal certainty perspective and examine the role of PPAT in implementing PMPJ in land sale and purchase transactions in Pekanbaru City. This research employs sociological or empirical legal methods through literature review and interviews with Land Deed Officials (PPAT) in Pekanbaru City. Data were analyzed qualitatively using legal certainty theory and authority theory to explain the legal position of PPATs and the implementation of PMPJ in practice. This approach was used to assess the extent to which PPATs act as administrative gatekeepers in preventing the entry of proceeds of crime into land transactions. The research results indicate that PPATs normatively act as administrative gatekeepers through the obligation to identify, verify, and monitor user transactions. However, this position does not fully reflect legal certainty because the PPAT's authority is limited to administrative aspects without the support of investigative instruments. In Pekanbaru City, the implementation of PMPJ has been carried out, but still faces obstacles such as limited reporting facilities, a lack of technical understanding, and concerns about reducing service user comfort. These conditions mean that the PPAT's role in preventing money laundering (TPPU) is suboptimal and requires more comprehensive regulatory support and technical guidance.